2018
DOI: 10.14745/ccdr.v44i78a06
|View full text |Cite
|
Sign up to set email alerts
|

Community outbreak of invasive group A streptococcus infection in Ontario, Canada

Abstract: Background: Outbreaks of invasive group A streptococcal infection (iGAS) have historically occurred in institutional settings. Increasingly, community-based outbreaks have been reported, often among marginalized populations, yet few guidelines exist for managing iGAS outbreaks in such settings. Objective: To describe the ongoing outbreak of iGAS in Middlesex-London, Ontario, and the challenges that arose while applying current guidelines to a marginalized population in a community setting. Methods: The outbrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…pyogenes requires 12 additional amino acids to be added to the minimal growth media to support its growth [3537]. Nevertheless S. pyogenes is an important pathogen in PWID with multiple outbreaks of disease associated with this organism, including in London, Ontario [38]. We suspect that crowding within homeless shelters, frequent soft tissue injury, as well as pre-injection practices (such as licking of the needle) may lead to these infections rather than contamination of the injectate.…”
Section: Discussionmentioning
confidence: 99%
“…pyogenes requires 12 additional amino acids to be added to the minimal growth media to support its growth [3537]. Nevertheless S. pyogenes is an important pathogen in PWID with multiple outbreaks of disease associated with this organism, including in London, Ontario [38]. We suspect that crowding within homeless shelters, frequent soft tissue injury, as well as pre-injection practices (such as licking of the needle) may lead to these infections rather than contamination of the injectate.…”
Section: Discussionmentioning
confidence: 99%
“…Second, despite the overlap in modes of acquisition/transmission between HIV/AIDS and hepatitis C and iGAS, specifically sharing of drug use equipment, there were only 59 clients in our dataset with all three disease types. Data from the aforementioned London, Ontario, iGAS outbreak investigation indicated that 9.5% of individuals (14/147) with iGAS infections were positive for both HCV and HIV (Dickson et al 2018 ). These individuals would represent 23.7% (14/59) of the clients with HCV, HIV/AIDS, and iGAS records in our dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of the iGAS cases in the outbreak were among marginalized populations, specifically in people who use drugs, people who are underhoused, or both. Many of the cases had hepatitis C (HCV) co-infections and a number of them had HCV-HIV co-infections (Dickson et al 2018 ).…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus pyogenes also called Group A Streptococcus (GAS), can produce an arsenal of extracellular secreted proteins to evade the innate immune system (Walker et al, 2014;Hynes and Sloan, 2016;Liu and Lei, 2018;Happonen et al, 2019). Although treated with modern medicine, it remains a significant cause of global morbidity and mortality (Dickson et al, 2018;Hua et al, 2019;Lynskey et al, 2019). Historically, many of these secreted proteins have been studied to find the mechanisms by which they facilitate the resistance against host defenses as well as to find possible candidate antigens for vaccines.…”
Section: Introductionmentioning
confidence: 99%